Polarisasi Keruangan Kabupaten Pelalawan: Analisis Geografis Ketersediaan Infrastruktur, Pola Pemukiman, dan Hierarki Tempat Sentral - Haura Fathia; Tiara Fajar Hartati; Melsa Chania; Silvi Sudarsih; Almegi (Mataram University, 2026)
This study aims to evaluate the availability of regional facilities and infrastructure, map the characteristics of settlement patterns, and analyze the position and functional interactions of villages within the urban system of Pelalawan Regency. The research employed a mixed methods approach, combining quantitative and qualitative descriptive analyses based on Geographic Information Systems (GIS). Data collection was conducted through three main techniques: literature review of official statistical documents such as Pelalawan Regency in Figures, field surveys (ground truthing), and structured interviews with key informants. The results of the spatial analysis using buffering modeling revealed significant disparities in the availability of public service facilities and the quality of road infrastructure among districts. The settlement patterns in Pelalawan Regency were identified into three main typologies, namely linear patterns following major road networks, linear patterns along the Kampar River, and agglomerated patterns surrounding plantation industrial areas or economic activity centers. Furthermore, based on the Scalogram Analysis and Village Development Index (VDI), the regional hierarchical structure in Pelalawan Regency is dominated by Pangkalan Kerinci District as the primary growth center (Hierarchy I), supported by 28 types of public service facilities. The resulting regional interaction pattern tends to reflect the characteristics of a primate city, where peripheral regions (Hierarchy III) remain highly dependent on the urban center. These findings highlight the importance of redistributing service functions and developing equitable connectivity infrastructure to achieve a balanced and sustainable urban system in Pelalawan Regency.